2015
DOI: 10.4238/2015.november.18.12
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus analysis for kernel width using maize recombinant inbred lines

Abstract: ABSTRACT. Maize (Zea mays L.) kernel width is one of the most important traits that is related to yield and appearance. To understand its genetic mechanisms more clearly, a recombinant inbred line (RIL) segregation population consisting of 239 RILs was used for quantitative trait locus (QTL) mapping for kernel width. We found four QTLs on chromosomes 3 (one), 5 (two), and 10 (one). The QTLs were close to their adjacent markers, with a range of 0-23.8 cM, and explained 6.2-19.7% of the phenotypic variation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…QTL for ear weight and kernel weight per ear co-mapped with the outlier loci in chromosome 3 (Yi et al 2019 ). QTL for ear diameter (Sabadin et al 2008 ), grain yield (Alves Lima et al 2006 ), hundred-kernel weight, kernel number per row (Chen et al 2016 ) and kernel width (Hui et al 2015 ; Chen et al 2016 ; Raihan et al 2016 ) co-mapped with the outlier in chromosome 5. QTL for grain yield per plant co-mapped with the outliers at 52.20 and 53.28 Mbp in chromosome 6 (Su et al 2017 ), while QTL for kernel width co-mapped with all outliers in chromosome 6 (Zhang et al 2014 ; Chen et al 2016 ) and the outlier at 135.91 Mbp in chromosome 10 (Hui et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTL for ear weight and kernel weight per ear co-mapped with the outlier loci in chromosome 3 (Yi et al 2019 ). QTL for ear diameter (Sabadin et al 2008 ), grain yield (Alves Lima et al 2006 ), hundred-kernel weight, kernel number per row (Chen et al 2016 ) and kernel width (Hui et al 2015 ; Chen et al 2016 ; Raihan et al 2016 ) co-mapped with the outlier in chromosome 5. QTL for grain yield per plant co-mapped with the outliers at 52.20 and 53.28 Mbp in chromosome 6 (Su et al 2017 ), while QTL for kernel width co-mapped with all outliers in chromosome 6 (Zhang et al 2014 ; Chen et al 2016 ) and the outlier at 135.91 Mbp in chromosome 10 (Hui et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…QTL for ear diameter (Sabadin et al 2008 ), grain yield (Alves Lima et al 2006 ), hundred-kernel weight, kernel number per row (Chen et al 2016 ) and kernel width (Hui et al 2015 ; Chen et al 2016 ; Raihan et al 2016 ) co-mapped with the outlier in chromosome 5. QTL for grain yield per plant co-mapped with the outliers at 52.20 and 53.28 Mbp in chromosome 6 (Su et al 2017 ), while QTL for kernel width co-mapped with all outliers in chromosome 6 (Zhang et al 2014 ; Chen et al 2016 ) and the outlier at 135.91 Mbp in chromosome 10 (Hui et al 2015 ). For the locus at 147.74 Mbp in chromosome 10 showing the strongest evidence for selection, co-locating QTL associated with ear length, kernel number per row (Huo et al 2016 ), cob and kernel length (Liu et al 2019 ), kernel volume, kernel weight (Zhang et al 2014 ), and kernel width (Hui et al 2015 ; Zhu et al 2018 ) were reported.…”
Section: Discussionmentioning
confidence: 99%